Evolution of approaches to measuring the level of globalisation of countries - Goloventchik, Galina G. (Journal of the Belarusian State University. Economics, 2021)
The article examines various methods of measuring globalisation. A new method of convolution of globalisation ratings is presented – a hybrid consensus rating of globalisation, according to which the top 20 countries of the world are identified by the level of globalisation and digitalisation. As a result, it is concluded that digital development greatly affects the level of globalisation of the country.